Climate Smart Investment Pathways for smallholder coffee farmers - International Institute of Tropical Agriculture (2019)
The Stepwise Climate Smart Investment Pathway (Stepwise) is an approach developed by the IITA research team in collaboration with partners. Stepwise breaks down the recommended best practices that many farmers cannot afford to implement into smaller, more affordable packages that can be implemented in phases. Stepwise considers specific agro-ecological variables and farmer needs and aspirations to guide incremental investment by the farmer in specific sets of, and timing of practices. This incremental investment is expected to subsequently increase coffee yields in a stepwise manner.